Chirality analysis of horizontally aligned single-walled carbon nanotubes: decoupling populations and lengths1. Issue 29 (7th August 2015) - Inoue, Taiki; Hasegawa, Daisuke; Chiashi, Shohei; Maruyama, Shigeo
<x xml:space="preserve">Abstract</x> Populations and lengths of single-walled carbon nanotubes with different chiralities (n, m) were evaluated by Raman mapping together with scanning electron microscopy.